Mothers’ involvement in their learning disabled children schooling - Barkauskienė, Rasa (Psichologija, 2003)
Problem: This study deals with mothers’ involvement in their learning disabled children schooling defined as different mothers’ activities: support for doing homework, negative control of homework, mother-child discussions about learning and school activities, child reinforcement for learning. Mothers’ involvement in child’s schooling is discussed in the light of family factors - mother’s feelings and attitudes toward the child, child’s "goodness of fit" to mother’s expectations, mother’s education level, family status and stressful life events - possibly related to particular forms of mothers’ involvement. Sample: Experimental group consisted of 92 primary school children (8-11 years old) diagnosed as learning disabled and control group - 90 average achievers from the same classes as children from experimental group. Evaluation tools: Mothers’ involvement with child?s learning was assessed via Mothers’ Involvement in Child’s Schooling Scale (constructed by author of article), mothers - feelings and attitudes toward the child - via Mothers - Feelings Scale (constructed by author of article), child’s "goodness of fit" to mother’s expectations - via technique recommended by Feagans and al. (1991). Data on family status, mother’s education level and family stressful life events were gathered through family questionnaire made by author of article. Results: Results revealed that mothers of learning disabled children are more controlling as well as give more positive reinforcement and support for child’s learning when compared to mothers of average achievers. Mothers of learning disabled children report higher degree of dissatisfaction with themselves as mothers as well as more negative feelings toward child. Mother’s positive feelings toward child and child’ high fit within mother’s expectations positively correlated with child reinforcement, mother-child discussions about learning and school as well as with general level of mother’s involvement in child’s schooling. Negative control of homework was higher when child’s fit within mother’s expectations was low. Negative control had positive statistically significant correlation with mother’s negative feelings toward child. Other family features such as stressful live events, family status is to be considered in the examination of mother’s involvement with their learning disabled children schooling.